Pocket Handbook of GI Pharmacotherapeutics - Pappano, Achilles; Wu, George Y.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2009)
Although there are many pharmacology texts, and electronic sources of drug information relating to GI disorders, they are frequently encyclopedic, and practical information can be difficult to find. In Pocket Handbook of GI Pharmacotherapeutics, George Wu and Achilles Pappano create a text that combines the current treatment protocols and practical pharmacological information of prominent GI disorders for the first time. Chapters are disease specific, and contain treatment algorithms and therapy guides that present all the essential information in a compact, easy to reference handbook. The text contains practical clinical information in a highly accessible format, including keys for relative costs and the FDA pregnancy rating system for drug safety. Informative and unique, Pocket Handbook of GI Pharmacotherapeutics is a must have reference for any internist, gastroenterologist or general practioner who endeavors to provide better treatment of their patients.
Gastrointestinal Disease -- Peptic Disorders -- Gastrointestinal Bleeding -- General GI Motility Disorders -- Specific GI Motility Disorders -- Inflammatory Bowel Disease -- General GI Infections -- Specific GI Microbial Infections -- Liver Disease -- Hepatitis -- Cholestasis -- Hepatic Encephalopathy -- Pruritis -- Nutrition and Enzyme Deficiency.
Keywords: Medicine; Pharmacology; Gastroenterology; Medicine & Public Health; Gastroenterology; Pharmacology/Toxicology.; Electronic books